Economic Integration between ASEAN+5 Countries: Comparison of GDP - Kueh, Jerome Swee Hui; Puah, Chin Hong; Murphy, Lai Mattias (Munich University Library, 2010)
This study aims to investigate the causality direction of economic integration among ASEAN countries together with five other neighboring countries, namely Australia, China, Japan, New Zealand and South Korea. The analysis is based on the economic integration of GDP covering the sample period from 1967 to 2007. Empirical results from the Toda and Yamomoto (1995) Granger non-causality tests depicted the existence of bi-directional causality relationships between the GDP of ASEAN and China; GDP of ASEAN and Japan; GDP ASEAN and South Korea, and also GDP of ASEAN and New Zealand. This indicates that there is a great potential for ASEAN countries moving towards higher degree of economic integration via strengthening the relationship with those countries within the region.